Ion desolvation for boosting the charge storage performance in Ti3C2 MXene electrode - Zheng Bo; Rui Wang; Bin Wang; Sanjay Sunny; Yuping Zhao; Kangkang Ge; Kui Xu; Yajing Song; Encarnacion Raymundo-Piñero; Zifeng Lin; Hui Shao; Qian Yu; et al. (Nature Communications)
Abstract Clarifying the relationship between ion desolvation, ion-electrode interactions, and charge storage capacity during ion intercalation in host electrode materials is crucial for advancing fast and efficient energy storage systems. However, the absence of direct evidence for ion desolvation and lack of detailed understanding of the interactions between surface terminations and intercalated cations (Li ions)/solvents hinder the exploration of their effects on energy storage mechanisms. In this paper, we study the intercalation of Li ions from a non-aqueous electrolyte in two-dimensional metal carbides Ti3C2 MXenes with different surface chemistries: HF-Ti3C2 (F-, OH- and O-terminated) and MS-Ti3C2 (O- and Cl-terminated) MXenes. We are able to visualize the full ion desolvation and solvents-ions co-intercalation in the interlayers of MS-MXene and HF-MXene, respectively at the atomic scale. The combination of several techniques and characterization tools reveal that the complete ion desolvation in Cl- and O-terminated MS-Ti3C2 MXenes is associated with the formation of a dense solid electrolyte interface layer, resulting in improved charge storage capacity. The O-rich surface terminations of MS-MXenes are found to be responsible for the efficient Li ions storage. These findings shed lights on identifying the critical role of non-electrostatic ion-electrode interactions and ion desolvation in designing high-performance energy storage devices.